Composition for expressing structural color

A core-shell structure using inorganic particles and catechol-iron complexes stabilizes structural colors, overcoming material variability issues and enabling bright, adjustable hues for diverse industrial uses.

JP7604878B2Active Publication Date: 2024-12-24DIC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020212265
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-22
Publication Date
2024-12-24
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

Existing structural color technologies using natural materials face challenges in producing a stable core-shell structure and achieving bright, controlled reflection wavelengths due to variations in material properties.

Method used

A composition comprising a core part made of inorganic material particles and a shell part containing a catechol group and iron, which forms a complex to enhance color development and stability, allowing for controlled reflection wavelengths.

Benefits of technology

The composition enables the expression of versatile structural colors with adjustable hues and designs, suitable for various industrial applications including cosmetics, coatings, and inks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604878000002
    Figure 0007604878000002
  • Figure 0007604878000001
    Figure 0007604878000001
Patent Text Reader

Abstract

To provide a highly versatile composition for structural color expression capable of creating a stable core shell structure and expressing vivid structural colors while controlling reflect wavelength regardless of material variations peculiar to natural materials.SOLUTION: The composition for structural color expression includes: a core part that includes inorganic material particles; and a shell part that contains a compound containing a catechol group. The compound that contains a catechol group and the shell part that contains iron are brown to black absorb scattered light and enhance the color development of the structural color. The composition for structural color expression is capable of easily controlling the reaction more than conventional polymerization reaction and is suitable for industrialization.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for expressing structural color. [Background technology]

[0002] Structural color is a coloring that does not use dyes, pigments, or other coloring matter, but is an optical effect that occurs due to the periodic structure of a multilayer film that exhibits a regular structure equivalent to the wavelength of light, the interference of light, and the selective reflection of circularly polarized light. Examples include the coloring of the surface of a CD, soap bubbles, and iridescent beetles. While dyes and pigments produce color by absorbing light of specific wavelengths, structural color produces color by selectively reflecting light of specific wavelengths using a regular structure. A feature of structural coloring is that it will not fade unless the regular structure is destroyed, and its application to commercial purposes is expanding. Furthermore, unlike petroleum-derived synthetic dyes and pigments, by controlling the ordered structure it is possible to produce a variety of colors using only natural materials, and this technology has attracted attention as a potential means of producing sustainable color materials that are kind to the environment and the human body.

[0003] A conventional structural color technology is a structural color technology that uses core-shell particles (Patent Document 1). This technology has the characteristic of being able to express various hues and designs such as matte and glitter tones with a single material system. However, the core material uses polystyrene, a synthetic material derived from petroleum, and neither the core material nor the shell material uses natural materials.

[0004] On the other hand, in Non-Patent Document 1, core-shell particles based on the same concept as Patent Document 1 are produced from natural materials, with the core particles being mainly composed of silica, which is found inexhaustibly on Earth, and the shell being made of iron tannate obtained from plant-derived tannic acid and iron.

[0005] However, when producing structural color materials using natural materials, particularly when natural materials are used for the shell material, it is difficult to produce a stable core-shell structure due to material variations specific to natural materials, and there is room for improvement in terms of expressing vivid structural colors with controlled reflected wavelengths. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-62271 A [Non-Patent Document 1] Sakai, M.; Seki, T.; Takeoka, Y. Colorful Photonic Pigments Prepared by using Safe Black and White Materials. ACS Sustainable Chem. Eng. 2019, 7, 14933-14940 Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is to provide a highly versatile composition for expressing structural color, which is capable of producing a stable core-shell structure and expressing vivid structural colors with controlled reflection wavelengths, even when natural materials are used, regardless of the material variations and the like that are specific to natural materials. [Means for solving the problem]

[0008] As a result of intensive research by the inventors to solve the above problems, they discovered that in a structural color generating composition having a core portion containing inorganic material particles and a shell portion containing a compound containing a catechol group and iron, the shell portion containing the compound containing a catechol group and iron is brown to black in color, thereby absorbing scattered light and enhancing the color development of the structural color. Furthermore, the inventors discovered that the reaction is easier to control than the polymerization reaction of the conventional technology and is suitable for industrialization, thereby solving the above problems with the structural color generating composition.

[0009] That is, the present invention includes the following.

[0010] [1] A composition for expressing structural color having a core-shell structure, A core portion including inorganic material particles; A shell portion containing a compound having a molecular weight of 110 or more and 1,000 or less containing a catechol group and iron; A composition for expressing structural color comprising the compound. [2] The composition for expressing structural color according to [1], wherein the inorganic material is at least one selected from the group consisting of silica, alumina, zirconia, titania, boron nitride, calcium carbonate, and zinc oxide. [3] The composition for expressing structural color according to [1] or [2], wherein the compound containing a catechol group and having a molecular weight of 110 or more and 1,000 or less is at least one compound selected from the group consisting of hematein, gallic acid, propyl gallate, chlorogenic acid, and carminic acid. [4] The composition for expressing structural color according to any one of [1] to [3], characterized in that the compound containing a catechol group and having a molecular weight of 110 or more and 1,000 or less forms a complex with iron and is adsorbed onto inorganic material particles. [5] The structural color generating composition according to any one of [1] to [4], wherein the inorganic material particle diameter of the core portion is 100 to 500 nm, and the shell portion has a thickness of 1 to 30 nm. [6] A structural color exhibiting material or structural color exhibiting particles, in which the structural color exhibiting composition according to any one of [1] to [5] is arranged in a resin. Effect of the Invention

[0011] The structural color-producing composition of the present invention has the characteristic of being able to produce a variety of hues and designs (matte tones, glitter tones), and can be used as a coloring material in a wide range of industrial fields, such as pigments for cosmetics, coating materials for pharmaceuticals or agricultural chemicals, edible pigments, pigments for food packaging inks, printing markers, stationery, writing instruments, inkjet inks, metallic inks, paints, plastic colorants, pigments for color toners, and chemical sensors. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram of a structural color-producing composition having a core-shell structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The embodiments of the present invention described below are merely some of the embodiments, and the present invention is not limited to the described contents as long as the gist of the invention is not significantly deviated from.

[0014] The structural color developing composition of the present invention has a structure of a core portion forming a central portion and a shell portion covering the outer periphery thereof.

[0015] [Core] The core portion of the present invention is composed of inorganic material particles. The inorganic material particles used in the present invention can control the hue of the structural color-producing composition by adjusting the average particle diameter. Specifically, the reflection wavelength of the structural color-producing composition can be estimated by substituting the average particle diameter and refractive index of the inorganic material particles into the Bragg formula. From the viewpoint of producing a more vivid chromatic color, the average particle diameter is preferably 100 to 500 nm, and more preferably in the range of 150 to 400 nm.

[0016] The CV value (coefficient of variation) indicating the monodispersity of the particle size distribution is a value obtained by using the standard deviation σ in the particle size distribution and the average particle diameter D, as follows: CV[%]=(σ / D)×100. The smaller this value, the narrower the particle size distribution and the more uniform the particle diameter. If the CV value is 10% or less, more preferably 5% or less, the color development of the structural color expression composition is improved.

[0017] The inorganic material particles used in the present invention may be a single particle, a mixture, or a combination. The particle form may be any of a single structure, a core-shell type, a multi-layer type, and a hollow particle. These may be used alone or in any combination of two or more types. In addition, it is preferable that the inorganic material particles are less likely to settle over time and have excellent color development properties.

[0018] Examples of inorganic material particles used in the present invention include, but are not limited to, silica, alumina, zirconia, titania, boron nitride, calcium carbonate, zinc oxide, etc. These may be used alone or in any combination of two or more.

[0019] The inorganic material particles used in the present application may be coated with an adhesive or the like to improve adhesion to the compound constituting the shell. When an adhesive or the like is used, it is preferable to use an adhesive that does not adversely affect the appearance of the structural color.

[0020] [Shell] The shell portion of the present invention contains a compound containing a catechol group and iron. Examples of compounds having a catechol group include hematein, gallic acid, propyl gallate, chlorogenic acid, carminic acid, and the like. The molecular weight is from 110 to 1000, and more preferably from 150 to 500. The compounds having a catechol group may be used alone or in combination. Among them, hematein is preferably used from the viewpoint of excellent adsorption to inorganic material particles.

[0021] The shell portion is the outer periphery of the core portion, and its thickness is preferably 1 to 30 nm, and more preferably 1 to 20 nm, taking into consideration that if it is too thin, it will not be able to absorb scattered light sufficiently, resulting in a whitish hue and poor color development of the structural color, and if it is too thick, it will absorb too much incident light, resulting in a blackish hue and poor color development of the structural color. By controlling the thickness in the thin direction within the above range, the surface unevenness of the structural color expressing composition having a core-shell structure is reduced, and the arrangement structure is more likely to become a colloidal crystal structure when the structural color pellet is produced. As a result, it is possible to obtain a glitter-like rainbow structural color in which the color changes depending on the observation angle due to Bragg diffraction of the incident light. On the other hand, if the thickness is controlled in the thick direction, the surface unevenness of the structural color expressing composition having a core-shell structure increases, and the arrangement structure is more likely to become an amorphous structure when the structural color pellet is produced. As a result, a matte monochrome structural color can be obtained in which the same color can be visually recognized regardless of the observation angle.

[0022] A compound containing a catechol group and having a molecular weight of 110 to 1000 forms an insoluble complex salt with a metal. Examples of metals that form insoluble complex salts include iron, aluminum, copper, tin, cobalt, and titanium. In the present invention, iron is used because the complex salt formed exhibits a brown to black color.

[0023] In the present invention, the shell is a material that covers the core as described above, and in combination with the core, it is possible to exhibit a highly color-developing structural color. An example of the mechanism of core-shell structure formation is shown below, but is not limited thereto. It is believed that an iron complex is formed between the hydroxyl groups on the surface of the inorganic material particles and the hydroxyl groups of a compound containing a catechol group and having a molecular weight of 110 to 1,000, forming a core-shell structure, or that the hydroxyl groups on the surface of the inorganic material particles and the hydroxyl groups of a compound containing a catechol group and having a molecular weight of 110 to 1,000 interact through hydrogen bonds to form a core-shell structure, or that both occur simultaneously.

[0024] Considering the above-mentioned presumed mechanism, it is preferable that the molar ratio of the compound containing a catechol group and having a molecular weight of 110 or more and 1000 or less to iron is contained in the shell at an equal or greater amount. Specifically, the molar ratio of the compound containing a catechol group and having a molecular weight of 110 or more and 1000 or less to iron may be 80:20 to 20:80, but is preferably 80:20 to 50:50.

[0025] Here, an example of a method for producing the structural color developing composition of the present invention will be described.

[0026] The method for producing the structural color expression composition of the present invention includes (1) dispersing inorganic material particles in a medium to prepare an inorganic material particle dispersion, and (2) adding a solution of an iron-containing compound and a solution of a compound containing a catechol group and having a molecular weight of 110 or more and 1,000 or less to the inorganic material particle dispersion, stirring the mixture, and covering the core portion containing the inorganic material particles with a shell portion containing the compound containing a catechol group and iron.

[0027] The inorganic material particles used in the present invention are dispersed in water or an organic solvent. Examples of the organic solvent include aromatic solvents such as toluene, xylene, and methoxybenzene, acetate ester solvents such as ethyl acetate, butyl acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate, propionate solvents such as ethoxyethyl propionate, alcohol solvents such as methanol, ethanol, propanol, n-butanol, isobutanol, and ethylene glycol, ether solvents such as butyl cellosolve, propylene glycol monomethyl ether, diethylene glycol ethyl ether, and diethylene glycol dimethyl ether, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aliphatic hydrocarbon solvents such as hexane, nitrogen compound solvents such as N,N-dimethylformamide, γ-butyrolactam, n-methyl-2-pyrrolidone, aniline, and pyridine, lactone solvents such as γ-butyrolactone, and water. Among these, water, ethanol, and ethylene glycol are preferable from the viewpoint of dispersibility of inorganic material particles. Also, the concentration of inorganic material particles during the preparation of the core-shell structure is preferably 0.01 to 1.0% from the viewpoint of dispersion stability.

[0028] Examples of compounds containing iron include ferrous sulfate, ferrous chloride, ferrous acetate, ferrous phosphate, ferrous oxalate, ferric sulfate, ferric chloride, ferric acetate, etc. Among these, ferrous chloride and ferric chloride are preferred because of ease of handling, including post-treatment steps.

[0029] The method of adding the solution of the iron-containing compound and the solution of the catechol-containing compound having a molecular weight of 110 to 1000 may be any one, or the two solutions may be added in small amounts. In addition, the series of steps may be performed at room temperature or with heating.

[0030] The thickness of the shell portion can be appropriately controlled by the amount of the compound containing a catechol group and having a molecular weight of 110 to 1,000 and the compound containing iron added, or by the number of repetitions of the steps (1) and (2) of the manufacturing method for the structural color expressing composition.

[0031] The structural color expressing composition of the present invention may be used as it is in the form of a dispersion containing the obtained structural color expressing composition, or may be used as a powder obtained by filtering and drying. The filtering and drying methods may be any of the usual methods and devices, and are not limited thereto.

[0032] The structural color expressing composition of the present invention can also be handled like a pigment. As an example, the structural color expressing composition is dispersed and aligned in a solvent containing a polymerizable substance, and the polymerizable substance is polymerized to obtain a structural color expressing material in which the structural color expressing composition is fixed. For example, by crushing this material to a certain size, spherical particles or flaky particles that emit structural colors can be obtained, and can be handled like a pigment.

[0033] By using the structural color generating composition of the present invention, various hues and designs (matte tone, glitter tone) can be generated, and it can be used as a coloring material in a wide range of industrial fields such as pigments for cosmetics, coating materials for pharmaceuticals or agricultural chemicals, edible pigments, pigments for food packaging inks, printing markers, stationery, writing implements, inkjet inks, metal inks, paints, plastic colorants, pigments for color toners, or chemical sensors. The applications detailed below are examples, and the structural color generating composition of the present invention can be used as a coloring material in any application.

[0034] (Cosmetic use) The structural color generating composition of the present invention can be used as a cosmetic. There is no particular limitation on the cosmetic used, and the structural color generating composition of the present invention can be used in various types of cosmetics.

[0035] The cosmetic may be any type of cosmetic as long as it can effectively exert its function. The cosmetic may be a lotion, cream gel, spray, etc. Examples of the cosmetic include skin care cosmetics such as face wash, makeup remover, skin lotion, beauty essence, pack, protective emulsion, protective cream, whitening cosmetics, and UV protection cosmetics, makeup cosmetics such as foundation, face powder, makeup base, lipstick, eye makeup, blusher, and nail enamel, hair care cosmetics such as shampoo, hair rinse, hair treatment, hair styling agent, permanent wave agent, hair dye, and hair growth agent, and body care cosmetics such as body cleansing cosmetics, deodorant cosmetics, and bath agents.

[0036] The amount of the structural color expressing composition of the present invention used in the cosmetic product can be appropriately set depending on the type of cosmetic product. The content in the cosmetic product is usually in the range of 0.1 to 99% by mass, and generally, it is preferable that the content is in the range of 0.1 to 10% by mass. On the other hand, in a makeup cosmetic product intended for coloring, the content is preferably in the range of 5 to 80% by mass, more preferably in the range of 10 to 70% by mass, and most preferably in the range of 20 to 60% by mass. When the amount of the structural color expressing composition of the present invention contained in the cosmetic product is in the above range, the function such as coloring can be effectively expressed, and the function required for the cosmetic product can be maintained.

[0037] The cosmetic may contain, depending on the type of cosmetic, in addition to the structural color-expressing composition of the present invention, a carrier, pigment, oil, sterol, amino acid, moisturizer, powder, colorant, pH adjuster, fragrance, essential oil, cosmetic active ingredient, vitamin, essential fatty acid, sphingolipid, self-tanning agent, excipient, filler, emulsifier, antioxidant, surfactant, chelating agent, gelling agent, thickener, emollient, moisturizer, moisturizer, mineral, viscosity adjuster, flow adjuster, keratolytic agent, etc., which are acceptable as cosmetic ingredients. These may include retinoids, hormonal compounds, alpha hydroxy acids, alpha keto acids, antimycobacterial agents, antifungal agents, antibacterial agents, antiviral agents, analgesics, antiallergic agents, antihistamines, anti-inflammatory agents, anti-irritants, antitumor agents, immune system boosters, immune system suppressants, antiacne agents, anesthetics, disinfectants, insect repellents, skin cooling compounds, skin protectants, skin penetration enhancers, exfoliants, lubricants, fragrances, dyes, bleaching agents, hypopigmenting agents, preservatives, stabilizers, pharmaceuticals, light stabilizers, and spherical powders.

[0038] The cosmetic product can be produced by mixing the structural color-producing composition of the present invention and other cosmetic ingredients. Furthermore, the cosmetic product containing the structural color-producing composition of the present invention can be used in the same manner as a normal cosmetic product, depending on the type of the cosmetic product, etc.

[0039] (Ink, paint applications) The structural color generating composition of the present invention can be used as ink or paint. However, the uses and compositions of the ink and paint will be described below, but the present invention is not limited thereto. The structural color generating composition of the present invention may be dispersed only in a thermoplastic resin, but it can also be dispersed in a printing ink vehicle or paint vehicle that contains a thermoplastic resin as an essential component.

[0040] As the thermoplastic resin, for example, polyester resin, polyamide resin, styrene resin, acrylic resin, polyolefin, polyalkylene terephthalate, polyvinyl chloride resin, or the like can be used as the dispersion resin.

[0041] For example, the vehicle for lithographic printing ink is produced from raw materials such as 20 to 50 mass% of resins such as rosin-modified phenolic resins, petroleum resins, alkyd resins, etc., 0 to 30 mass% of animal and vegetable oils such as linseed oil, tung oil, soybean oil, etc., 10 to 60 mass% of solvents such as n-paraffin, isoparaffin, naphthene, α-olefins, aromatics, etc., and a few mass% of other additives such as solubilizers and gelling agents.

[0042] Vehicles for gravure printing inks and flexographic printing inks are produced from raw materials such as 10 to 50 mass% of one or more resins selected from rosins, maleic acid resins, polyamide resins, vinyl resins, cyclized rubbers, chlorinated rubbers, ethylene-vinyl acetate copolymer resins, urethane resins, polyester resins, alkyd resins, nitrocellulose, cellulose acetate, etc., and 30 to 80 mass% of a solvent such as an alcohol, toluene, n-hexane, ethyl acetate, cellosolve, or butyl cellosolve acetate.

[0043] Vehicles for paints are produced from raw materials such as 20 to 80 mass % of resins such as alkyd resins, epoxy resins, acrylic resins, polyurethane resins, polyester resins, melamine resins, urea resins, and water-soluble resins, and 10 to 60 mass % of solvents such as hydrocarbons, alcohols, ketones, and water.

[0044] (Plastic applications) The structural color generating composition of the present invention can also be used for coloring plastics. When obtaining colored plastic molded products, thermoplastic resins (plastics) for thermoforming such as injection molding and press molding, such as polyolefins such as polyethylene and polypropylene, and polyvinyl chloride resins, are used, and the structural color generating composition of the present invention can be kneaded into these resins by a conventionally known method. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, "%" in the compositions means "% by mass".

[0046] [Method for measuring average primary particle size] The structural color pellets were photographed at 20,000 times magnification using a scanning electron microscope (Keyence Corporation, VE-7800) to obtain particle images. The longest length (maximum length) of the particle diameter of 50 primary particles that make up the aggregate on the two-dimensional image was then calculated. The average value of the maximum length of each particle was taken as the average particle diameter of the primary particles.

[0047] [Method of measuring reflection peak wavelength] The reflection spectrum of the prepared structural color pellet was measured using a spectroscopic characteristic measuring device (Otsuka Electronics Co., Ltd., LCF-100). The peak top value of the spectrum was taken as the reflection peak wavelength.

[0048] [Surface analysis of core-shell particles] The structural color pellets were crushed with a spatula to produce a powder sample, and the composition of the elements that make up the sample surface was measured using a scanning X-ray photoelectron spectrometer (ULVAC-PHI, Inc., Quantera SXM).

[0049] Example 1 0.22 g of Silbol 250 (Fuji Chemical Co., Ltd.), a silica particle, and 50 g of ethanol were added to a 200 mL recovery flask. The recovery flask was placed in an ultrasonic cleaner and operated for 1 hour to disperse the silica particles in the ethanol, producing liquid A. To a 50 mL beaker were added 9.54 g of ion-exchanged water and 0.46 g of iron (III) chloride solution (Kanto Chemical Co., Ltd., purity 34.0 to 36.0%), and a stirrer was added and the mixture was stirred for 10 minutes to prepare liquid B. To a 50 mL beaker, 16.5 g of ethanol and 0.10 g of hematein (Sigma-Aldrich Corporation, molecular weight 300.26) were added, and a stirrer was placed and stirred for 10 minutes to prepare liquid C. A stirrer was placed in the A solution, and while stirring with the stirrer, 0.50 g of the B solution was gradually added and stirred at room temperature for 30 minutes. Then, 2.5 g of the C solution was gradually added over 5 minutes and stirred at room temperature for 5 hours. After that, the three steps of centrifugation (9000G, 10 minutes), removal of the supernatant, and dispersion in ion-exchanged water were repeated five times until the supernatant became colorless and transparent, and an aqueous dispersion (1) (solid concentration 10%) of the structural color expressing composition was obtained. 0.1 mL of the obtained dispersion (1) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours. Due to its structural color, the color changed depending on the viewing angle, and when observed from the front, a glitter-like green pellet (1) was obtained.

[0050] Example 2 The same procedure as in Example 1 was repeated except that the amounts of B and C solutions added to A solution were changed to 1.5 g of B solution and 7.5 g of C solution, to obtain an aqueous dispersion (2) of a structural color-expressing composition (solid concentration: 10%). 0.1 mL of the obtained dispersion (2) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours, resulting in matte green pellets (2) whose color does not change even when viewed from different angles due to their structural color.

[0051] Example 3 0.22 g of Silbol 250 silica particles and 50 g of ion-exchanged water were added to a 200 mL recovery flask. The recovery flask was placed in an ultrasonic cleaner and operated for 1 hour to disperse the silica particles in the water, producing liquid D. To a 50 mL beaker were added 19.81 g of ion-exchanged water and 0.19 g of gallic acid monohydrate (Kanto Chemical Co., Ltd., molecular weight 170.12), and a stirrer was added and the mixture was stirred for 10 minutes with a stirrer to prepare solution E. A stirrer was placed in D solution, and while stirring with the stirrer, 8.0 g of B solution was gradually added and stirred at room temperature for 30 minutes. Then, 16.0 g of E solution was gradually added over 5 minutes and stirred at room temperature for 5 hours. After that, the three steps of centrifugation (9000G, 10 minutes), removal of the supernatant, and dispersion in ion-exchanged water were repeated five times until the supernatant became colorless and transparent, to obtain an aqueous dispersion (3) (solid concentration 10%) of the structural color expressing composition. 0.1 mL of the obtained dispersion (3) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours. Due to its structural color, the color changed when the viewing angle was changed, and when observed from the front, a glitter-like green pellet (3) was obtained.

[0052] Example 4 To a 50 mL beaker were added 19.29 g of ion-exchanged water and 0.71 g of chlorogenic acid (Tokyo Chemical Industry Co., Ltd., molecular weight 354.31), and a stirrer was added and the mixture was stirred for 10 minutes with a stirrer to prepare solution F. In Example 3, the same procedure as in Example 1 was carried out except that 0.50 g of B solution added to D solution and 0.50 g of F solution were added instead of C solution, to obtain an aqueous dispersion (4) of a structural color-expressing composition (solid concentration: 10%). 0.1 mL of the obtained dispersion (4) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours. Due to its structural color, the color changed depending on the viewing angle, and when observed from the front, a glitter-like green pellet (4) was obtained.

[0053] <Comparative Example 1> The same procedure as in Example 1 was repeated except that the amounts of B and C solutions added to A solution were changed to 0.05 g of B solution and 0.25 g of C solution, to obtain an aqueous dispersion (5) of a structural color-expressing composition (solid concentration: 10%). 0.1 mL of the obtained dispersion (5) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours, yielding white pellets (5) with a slight glittery appearance due to the structural color.

[0054] <Comparative Example 2> The same procedure as in Example 1 was repeated except that the amounts of B and C solutions added to A solution were changed to 4.5 g of B solution and 22.5 g of C solution, to obtain an aqueous dispersion (6) of a structural color-expressing composition (solid concentration: 10%). 0.1 mL of the resulting dispersion (6) was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours, yielding black pellets (6).

[0055] <Comparative Example 3> 1.0 g of Silbol 250 silica particles and 9.0 g of ion-exchanged water were added to a 200 mL recovery flask. The recovery flask was placed in an ultrasonic cleaner and operated for 1 hour to disperse the silica particles in the water, producing liquid G. 0.1 mL of Solution G was dropped onto a silicon rubber sheet and allowed to dry naturally for 24 hours, yielding white pellets (7) with a slight glittery appearance due to their structural color.

[0056] Structural color pellets (1)-(7) were measured with a scanning X-ray photoelectron spectrometer, and the amount of carbon detected was greater in structural color pellets (1)-(6) than in structural color pellet (7), which uses only the raw silica particles. In addition, iron was not detected in structural color pellet (7), but was detected in structural color pellets (1)-(6). In addition, in the images of the structural color pellets (1) to (7) taken with a scanning electron microscope, no substances with shapes other than particles of approximately equal size were observed. From the above, it is believed that in the composition for expressing structural color, the silica particles, the compound containing a catechol group and having a molecular weight of 110 or more and 1,000 or less, and the iron are not present separately, but have a core-shell structure having a core portion containing the silica particles and a shell portion containing the compound containing a catechol group and having a molecular weight of 110 or more and 1,000 or less, and iron.

[0057] The average particle size of the core-shell particles, the thickness of the shell part, and the reflection peak wavelength measured by a spectrophotometer are shown below, which are measured from particles observed by a scanning electron microscope. The thickness of the shell part is calculated by subtracting the average particle size of Comparative Example 3 (raw silica particles) from the average particle size of each core-shell particle, and dividing the result by 2.

[0058] [Table 1]

[0059] Comparing Examples 1 and 2 with Comparative Examples 1 to 3, the average particle size of the core-shell particles could be adjusted by adjusting the amount of hematein, which is a compound containing a catechol group and has a molecular weight of 110 to 1000. In other words, the thickness of the shell part of the core-shell structure could be adjusted. In Comparative Example 1, the shell was thin, and the scattered light was not absorbed by the shell, so the coloring due to the structural color was white and blurred. In Comparative Example 2, the shell was thick, and a lot of the incident light was absorbed by the shell, so it showed a brown to black color, and the coloring due to the structural color could not be observed with the naked eye. On the other hand, when the thickness of the shell portion was appropriately adjusted as in Examples 1 and 2, a matte or glittery structural color was expressed. As shown in Examples 3 and 4, compounds other than hematein that contained a catechol group and had a molecular weight of 110 or more and 1,000 or less were also adsorbed onto the surface of silica particles, forming a core-shell structure and exhibiting structural color. [Explanation of symbols]

[0060] (a): Core portion that forms the center, (b): Shell portion that covers the core portion.

Claims

1. In the composition for expressing structural color having a core-shell structure, A core portion including inorganic material particles; A shell portion containing iron and a compound having a molecular weight of 110 to 1,000 and containing at least one catechol group selected from hematein, gallic acid, propyl gallate, chlorogenic acid, and carminic acid, The structural color generating composition, wherein the inorganic material particle diameter of the core portion is 100 to 500 nm, and the thickness of the shell portion is 1 to 30 nm.

2. 2. The composition for expressing structural color according to claim 1, wherein the inorganic material is at least one selected from the group consisting of silica, alumina, zirconia, titania, boron nitride, calcium carbonate, and zinc oxide.

3. 3. The composition for expressing structural color according to claim 1, wherein the compound containing a catechol group and having a molecular weight of 110 to 1,000 forms a complex with iron, and the complex is adsorbed onto inorganic material particles.

4. A structural color expressing material or structural color expressing particle, comprising the structural color expressing composition according to any one of claims 1 to 3 arranged in a resin.

Citation Information

Patent Citations

  • Preparation method and application of catechol-containing polymer

    CN105017528A

  • Block copolymers for stable micelles

    JP2015512938A

  • Film containing core-shell particles, and article

    JP2017062271A

  • Negative electrode active material for lithium ion secondary battery, lithium ion secondary battery negative electrode arranged by use thereof, and lithium ion secondary battery arranged by use thereof

    JP2017183051A

  • Particle, decorative object, ink composition, method for producing ink composition, image forming method, and toner

    JP2018002929A